Pelembagaan Hukum Islam di Sumatera Timur: Tinjauan Historis - Jumanah Nasution; Zainul Fuad (UNES Law Review, 2023)
The institutionalization of Islamic law has long roots in the life history and collective memory of the Indonesian Muslim community; Reflected in various proverbs such as "Adat is coded syarak, syarak is coded Kitabullah" in Minangkabau and "Hukom ngon adat lagee alat ngon sifeut" in Aceh. Throughout the sultanates in Arkhabil, including North Sumatra, this institution grew during the era of the Islamic sultanates. In that period, fiqh literature became a source of reference for developing law, and the jurists occupied a central position at court in society as the intellectual elite. Simultaneously with the entrenchment of the colonial grip, Islamic law and its judiciary experienced decline and stunting until in the end they only handled matters of marriage, divorce and reconciliation with quasi authority. The Muslim community's long efforts to revitalize the enforcement of Islamic law found its momentum again in the Proclamation and was outlined in the Jakarta charter. Even though it was later deleted, it was considered implicit in Pancasila and the 1945 Constitution, which was reaffirmed through the Presidential Decree of 5 July. implementation of Islamic law for Muslims in the Republic of Indonesia and every sound request in that direction is legal. With his long experience of protecting various sects, races, ethnicities and religions in a wide geography from Morocco to Merauke, for at least 13 periods, the discourse of fiqh in its broadest meaning is expected to be able to contribute to modern life in building peace in pluralism.